Review: Linda Dale Bloomberg & Marie F. Volpe (2008). Completing Your Qualitative Dissertation: A Roadmap From Beginning to End - Janette Young; Richard McGrath; Shaun Filiault (Forum: Qualitative Social Research, 2009)
In writing an overarching book aimed at addressing the needs of all qualitative doctoral researchers, BLOOMBERG and VOLPE have produced a volume that offers many tools and ideas that are of value to doctoral dissertation students. However, the publication is not without its limitations: it is underpinned by an unarticulated, positivist approach to qualitative research, and presumes readers will at least be familiar with the system of doctoral dissertations undertaken in the United States of America. URN: urn:nbn:de:0114-fqs0903163